2011
DOI: 10.1590/s1517-83822011000300019
|View full text |Cite
|
Sign up to set email alerts
|

Membrane permeability alteration of some bacterial clinical isolates by selected antihistaminics

Abstract: Several antihistaminics possess antibacterial activity against a broad spectrum of bacteria. However, the exact mechanism of such activity was unclear. Hence, the aim of this study is to investigate their mechanism of antibacterial activity especially their effect upon the permeability of the bacterial cytoplasmic membrane.The effects of azelastine, cetirizine, cyproheptadine and diphenhydramine were studied using Gram-positive Furthermore, the effect of pretreating certain isolates for both short and long per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 3 publications
(3 reference statements)
1
19
0
Order By: Relevance
“…Alteration of membrane permeability is one of the major mechanisms underlying the drug tolerance phenomenon, and damage to the cell wall should affect overall cell permeability (28). We found that the cell membrane became permeable to a membrane-impermeant dye, PI (29), when cells were exposed to CUR along with CWP agents at synergistic concentrations.…”
Section: Discussionmentioning
confidence: 86%
“…Alteration of membrane permeability is one of the major mechanisms underlying the drug tolerance phenomenon, and damage to the cell wall should affect overall cell permeability (28). We found that the cell membrane became permeable to a membrane-impermeant dye, PI (29), when cells were exposed to CUR along with CWP agents at synergistic concentrations.…”
Section: Discussionmentioning
confidence: 86%
“…Azelastine has been previously shown to induce alterations in the bacterial membrane permeability (6). This was demonstrated by induction of leakage of bacterial intracellular materials, damage to bacterial membranes as shown by TEM, and damage to negatively charged cholesterol-free unilamellar liposomes, an artificial membrane model.…”
Section: Resultsmentioning
confidence: 97%
“…Azelastine is a phthalazinone non-sedating new generation antihistaminic drug widely used in the management of allergic conditions. Azelastine possesses certain antibacterial activity against a variety of microorganisms (5) due to its ability to induce alterations in membrane permeability and disruption of its integrity as previously shown (6). However, its interaction with antibiotics was not reported in the literature.…”
mentioning
confidence: 95%
“…11 Saponins work by damaging the cytoplasmic membrane by reducing surface tension resulting in increased cell permeability and leakage resulting in intracellular compounds coming out. 12 The mechanism of action of phenolic as an antibacterial is poisoning protoplasm, damaging and penetrating walls and depositing bacterial cell proteins. Large molecular phenolic compounds are capable of activating essential enzymes in bacterial cells even in very low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of the tannin as an antibacterial is to inhibit the reverse transcriptase and DNA topoisomerase enzymes so that the DNA transcription process is disrupted and new bacterial cells cannot be formed. 12…”
Section: Discussionmentioning
confidence: 99%